Betaine increases the butyrylcholinesterase activity in rat plasma - Šišková, Katarína; Dubničková, Martina; Pašková, Ľudmila; Rajdl, Daniel; Ďuračková, Zdeňka; Muchová, Jana; Pauliková, Ingrid; Racek, Jaroslav (Physiological research, 2016)
The physiological function of butyrylcholinesterase (EC 3.1.1.8, BChE) is not clearly understood, but a role was suggested in the fat utilization process, resulting in positive correlation between plasma triglyceride (TG) levels and BChE activity. Consequently we tested the hypothesis that regular intake of betaine, a natural compound intervening in the liver TG metabolism could influence the BChE activity. The BChE activity was estimated spectrophotometrically in plasma of rats fed with betaine enriched standard (B) or high-fat diet (HFB). The results confirmed decreased TG plasma levels after betaine treatment independently on the type of diet (0.15+/-0.03 (B) vs. 0.27+/-0.08 (control) mmol/l; p=0.003 and 0.13+/-0.03 (HFB) vs. 0.27+/-0.08 (control) mmol/l; p=0.005). The BChE activity increased significantly with betaine administration, however the change was more distinct in the HFB group (0.84+/-0.34 (HFB) vs. 0.22+/-0.04 (control) O.D./min/mg; p<0.001 and 0.41+/-0.11 (B) vs. 0.22+/-0.04 (control) O.D./min/mg; p=0.001). In conclusion, betaine intake led to elevated BChE activity in plasma and this effect was potentiated by the HF diet. Since betaine is in general used as a supplement in the treatment of liver diseases accompanied by TG overload, its impact on the BChE activity in the role of the liver function marker should be taken into account.
Keywords: aktivace enzymů; Animals; Butyrylcholinesterase; butyrylcholinesterasa; nemoci jater; Rats, Wistar; Enzyme Activation; triglyceridy; Diet, High-Fat; Triglycerides; betain; Liver Diseases; Male; krysa rodu Rattus; zvířata; mužské pohlaví; dieta s vysokým obsahem tuků; Betaine; Rats; potkani Wistar